2019
DOI: 10.1038/s41420-019-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

The prodomain of caspase-3 regulates its own removal and caspase activation

Abstract: Caspase-3 is a cysteine–aspartic acid protease that cleaves cellular targets and executes cell death. Our current understanding is caspase-3 is activated by the cleavage of the interdomain linker and then subsequent cleavage of the N-terminal prodomain. However, previous reports have suggested that removal of the prodomain can result in the constitutive activation of caspase-3, although other studies have not observed this. To address this question in a more physiological setting, we developed an inducible dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 25 publications
1
54
0
3
Order By: Relevance
“…Caspases (aspartate-specific cysteine proteases) are a family of protease enzymes with fate-determining roles involved in many cellular processes, including programmed cell death, differentiation, neuronal remodeling, and inflammation [ 38 ]. During apoptosis, caspase-3 (i.e., a major executioner caspase) is cleaved at an aspartate residue to yield a p12 and a p17 subunit to form the active caspase-3 enzyme [ 39 ], resulting in the cleavage of key structural proteins, cell cycle proteins, and DNase proteins, such as poly (ADP-ribose) polymerase, gelsolin, ICAD/DFF, and DNA-dependent kinase [ 40 ]. When SK-MEL-2 cells were treated with 50 μg/mL BF, caspase-3 activity was strongly increased ( Figure 2 B), indicating that BF induced cell death via caspase-3 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Caspases (aspartate-specific cysteine proteases) are a family of protease enzymes with fate-determining roles involved in many cellular processes, including programmed cell death, differentiation, neuronal remodeling, and inflammation [ 38 ]. During apoptosis, caspase-3 (i.e., a major executioner caspase) is cleaved at an aspartate residue to yield a p12 and a p17 subunit to form the active caspase-3 enzyme [ 39 ], resulting in the cleavage of key structural proteins, cell cycle proteins, and DNase proteins, such as poly (ADP-ribose) polymerase, gelsolin, ICAD/DFF, and DNA-dependent kinase [ 40 ]. When SK-MEL-2 cells were treated with 50 μg/mL BF, caspase-3 activity was strongly increased ( Figure 2 B), indicating that BF induced cell death via caspase-3 activation.…”
Section: Resultsmentioning
confidence: 99%
“…4C ). It has been reported that caspase-3 is a cysteine-aspartic acid protease that will be cleaved by TRAIL and executes apoptosis in cancer cells ( 36 , 37 ). Therefore, the present study monitored the levels of cleaved caspase-3 in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the prodomain of CASP3 is not yet fully understood. In the cellular context, it has been suggested that the prodomain is involved in the regulation of CASP3 activity and CASP3 mutants lacking the prodomain exhibit a lower activation threshold [21]. Therefore, we included a construct without the N-terminal prodomain in our study.…”
Section: Resultsmentioning
confidence: 99%